Micropolitics in smooth and sticky events of mundane school life - Anna Kristiina Kokko; Maiju Paananen; Laura Hirsto (Nordic Journal of Studies in Educational Policy, 2024)
ABSTRACTThis study contributes to the discussion of children’s participation in educational practices. In particular we are interested from the moments that reach beyond formal modes of participation. For this purpose, we use the concept of micropolitics and examine happenings in which children’s actions collide with everyday school practices and larger social and political surfaces. The data consist of one year-long ethnographic fieldwork produced in two Finnish comprehensive schools. Based on the analysis, we identified two different types of events – ‘smooth’ and ‘sticky’ – to which micropolitics entangled. Identifying these two types of events aids us in understanding the kinds of situations in which children have or do not have political power in their everyday school lives. Our analysis show that children take part in discussing wide societal issues, such as social class and local education policies, but it raises questions about the ability of schools as institutions to recognize children’s initiatives. Based on the findings, we propose that the concept of micropolitics can be particularly useful in understanding why some modes of participation become difficult and stay hidden while others are easier to recognize.